PRODUCT RANKING: MEASURING PRODUCT REVIEWS ON THE PURCHASE DECISION - Ahmad Johan; Barkah Rosadi; Tezza Adriansyah Anwar (Journal of Business Studies and Management Review, 2021)
The development of the digital world today has had a significant impact on the industrial sector, one of which is the development of e-commerce. E-commerce is one of the platforms used by consumers in searching for information related to the needs of both products or services. Rating of a product plays an important role that can help consumers to support purchasing decisions and reduce search costs. Many factors can influence online purchasing decisions such as ewom, celebrity influencers, and online discounts, but very few studies have examined product ratings in determining purchasing decisions. This study aims to obtain results regarding the effect of product rating and web quality on purchasing decisions among private university students in Bandung. This type of research is an explanatory research that intends to explain the position of the variables studied and the relationship between one variable and another. The sample used in this study was 100 6th semester students with a focus on 3 classes of business and management faculty. The results showed that there was an influence between product rating and web quality variables on purchasing decisions. Although the results show that the effect is not large enough, these two factors, especially product ratings, are one of the variables that are often used by consumers in supporting online purchasing decisions.